PENGARUH KUALITAS LAYANAN DAN PENANGANAN KOMPLAIN TERHADAP KEPUASAN NASABAH PADA LOYALITAS NASABAH PADA BANK BRI CABANG KERTAJAYA DI SURABAYA - SALAY, VICTOR (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The main objective of this research is to analysis the factors that influence customer loyalty. The object of this research is Bank Rakyat Indonesia Surabaya Kertajaya Branch. The research problems are refer to the business phenomena in Bank Rakyat Indonesia Surabaya Kertajaya Branch and some research gap based on previous researches. Therefore, the research problems are: â€œHow to develop a customer loyalty, could be achieved complied with the particular expectationâ€. The purpose of this research is to investigated the path of customer loyalty. Formulated models this research aim to give critical understanding in concept and measurement of customer loyalty. This research measure service quality, complain management, and customer satisfaction as antecedents and have consequence to customer loyalty. Besides the theoretical model, the researcher subsequently had compiled three hypothesis for this research. Purposive method had been used to gain valuable data in this study. Researcher used 100 respondents and all of them are customer of Bank Rakyat Indonesia Surabaya Kertajaya Branch. All data of this researched had been analyzed by Structural Equation Model with computer program Lisrel 8.80. The main findings of this research showed that service quality has a positive impact on customer satisfaction. Complain management also has a positive impact on customer satisfaction. The main conclusions of this research is that the influence of customers satisfaction towards customer loyalty had a significant (positive) impact. The final conclusion of customer loyalty research can be recommended as crucial implications for management. Researcher believe that the approach used in this study can help bank managers gain useful insight regarding the relative contribution of each of specific complain management dimension to the customer satisfaction, and customer loyalty.